Assessment of an innovative plug and play PV/T system integrated in a prefabricated house unit: Active and passive behaviour and life cycle cost analysis. (March 2022) - Vassiliades, C.; Barone, G.; Buonomano, A.; Forzano, C.; Giuzio, G.F.; Palombo, A.
Abstract: This paper aims to examine the integration of a hybrid photovoltaic/thermal (PV/T) solar system in an energy efficient, environmentally friendly, and technologically advanced prefabricated housing unit, to be considered as a cost and energy-saving solution of green construction. The study focuses on the energy production potential of the active solar system, in relation to the energy requirements of the housing unit, before and after the system's integration. For the energy and economic assessment of the proposed unit, a numerical investigation is developed in TRNSYS environment, in which the thermal and electrical behaviour of the coupled system – prefabricated house integrating the PV/T device - is conducted through dynamic simulations performed under Mediterranean and semi-continental climate conditions. Simulations are performed by considering the proposed prefabricated house with two modular wall units with and without integrating PV/T panels. A life cycle cost analysis is also developed to determine the viability of the enterprise, based on the only changing parameter between the reference (without PV/T) and the proposed case (with PV(/T). The results of the energy simulations and the life cycle cost analysis of the system are intended to assess the impact of the PV/T modules integration on the energy, economic, and comfort performance of the prefabricated building unit. Simulation results show that the proposed configuration leads to primary energy savings up to 548% for Larnaca, Cyprus, and up to 180% for Bolzano, Italy. It is observed that the energy savings are mainly due to the active effect of the proposed system (electricity production by solar renewable energy) that allows obtaining simple pay back periods ranging from 6.1 to 9.1 years for the simulated scenarios.